تأثير بعض عوامل التصنيع على إنضاج الجبن الأبيض ( العكاوي ) المخزن في محلول ملحي - منصور أحمد; حرفوش محسن; حلبي كاميليا (Latakia University Journal -Biological Sciences Series, 2014)
هدفت هذه الدراسة إلى تحديد التأثيرات المختلفة لبعض عوامل التصنيع على معدل الإنضاج وأهم خصائص الجبن الأبيض السوري ( العكاوي ) , حيث صنع الجبن مخبرياّ من حليب مبستر على 72 مْ لمدة 15 ثانية بإتباع الطرق التقليدية المعروفة و حفظ الجبن بتراكيز ملحية 12 و 16 % على حرارة البراد و حرارة الغرفة لمدة 60 يوم , وتمّ تتبع بعض التغيرات الفيزيوكيميائية والبيوكيميائية التي حصلت خلال فترة التخزين , حيث وجد أن للتراكيز الملحية المختلفة و درجات الحرارة و زمن التخزين تأثيراً معنوياً على المادة الجافة و البروتين و الدهن والرماد و الملح وpH والآزوت الكلي و الذائب و معامل الإنضاج و ذلك عند مستوى معنوية 5 %. إذ تبين أنّ معامل الإنضاج في الجبن المخزن على حرارة الغرفة و بتركيز ملحي 12 و 16 % كان 21.42 و 17.77 % على التوالي , في حين معامل الإنضاج للجبن المخزن على حرارة البراد و بتركيز ملحي 12 و 16 % كان 12 و 9.34 % على التوالي و ذلك في نهاية فترة الإنضاج . The aim of this study was to determine the effect of different manufacturing factors on ripening rates and important properities of Syrian White cheese(AKawei) . Cheese was made from pasteurized milk ( 72 °C for 15 Sec , using traditional way ) were stored in 12 , 16 % Brine for 60 days at room and fridge temperatures. Some physicochemical and biochemical analyses were carried out during storage time. . The effect of different brine concentrations, temperatures and ripening time on total solids, protein, ash, salt, fat, pH,total and solves nitrogen and ripening rates were found to be statically significant at (P<0.05).The result indicated that ripening rates for cheese stored in 12 , 16 % Brine at room temperature were 21.42 % and 17.77 % respectively . While the ripening rates for cheese stored in 12 , 16 % Brine at fridge temperature were 12 % and 9.34 % respectively at the end of ripening time .